Keabsahan Perjanjian Sewa Menyewa Terhadap Objek Harta Bersama Setelah Adanya Perceraian (Studi Kasus Putusan Nomor 667/Pdt.G/2023/PN.Jkt.Sel) - Panji Ramadhan; Ariawan Gunadi (Dinasti Review Publisher, 2024)
This research discusses the validity of rental agreements for joint property objects after divorce, with a case study of the divorce between Yosephin Evylia Dewi (YED) and Paulus Trijanto Adi Wibowo (PTAW) in Jakarta in 2021. This case illustrates the complexities that arise when joint property , which in this case is a house, is rented by one party without the consent of the other party. Based on Marriage Law Number 1 of 1974, every legal action related to joint property requires approval from both parties. Rental agreements entered into without this approval give rise to several legal consequences, including the potential for the agreement to be null and void and losses for the tenant. This study emphasizes the importance of mutual agreement in managing joint assets to avoid legal disputes and provide legal certainty for all parties involved.